PHACE syndrome misdiagnosed as a port-wine stain. (15th July 2015) - Thomson, Jason; Greig, Aina; Lloyd, Claire; Morrison, Danny; Flohr, Carsten
Abstract : We present the case of a boy born with a large macular, segmental vascular anomaly over the left face, initially diagnosed as a capillary malformation (port-wine stain) by the postnatal paediatric team. The vascular anomaly in the face then grew rapidly during the first few weeks of life and started to occlude the left eye, causing parental concerns about the infant's vision. A dermatological opinion established that the lesion was a segmental infantile haemangioma (IH). This, in combination with the posterior fossa malformation previously detected on antenatal scanning and confirmed by an MRI postnatally, satisfied the criteria for P osterior fossa abnormalities, H aemangiomas, A rterial abnormalities, C ardiac abnormalities and E ye abnormalities (PHACE) syndrome: a rare cutaneous neurovascular syndrome. This case highlights the diagnostic challenge posed by early phenotypes of haemangiomas as well as the importance of correctly diagnosing PHACE syndrome.